Zonal differences in meniscus MR relaxation times in response to in vivo static loading in knee osteoarthritis. Issue 2 (12th August 2015) - Calixto, Nathaniel E.; Kumar, Deepak; Subburaj, Karupppasamy; Singh, Justin; Schooler, Joseph; Nardo, Lorenzo; Li, Xiaojuan; Souza, Richard B.; Link, Thomas M.; Majumdar, Sharmila
ABSTRACT: This study assessed the effects of static loading on MRI relaxation times of menisci in individuals with and without radiographic knee OA. High‐resolution fast spin‐echo (FSE) and T1 ρ /T2 relaxation time MR sequences were obtained with and without loading at 50% body weight in 124 subjects. T1ρ /T2 relaxation times were calculated in menisci, and meniscus lesions were assessed through clinical grading. Student's t ‐test compared OA and control unloaded relaxation times as well as within‐group changes with loading, Generalized Linear Models evaluated zonal variation, and ANCOVA compared loading response between groups. Unloaded T1ρ and T2 in the middle and inner zones of the lateral anterior horn and outer zone of the medial posterior horn were significantly higher in OA and suggest that meniscal OA change occurs unevenly. Zonal T1ρ and T2 showed differing patterns between anterior and posterior horns, suggesting differences in macromolecular organization. Significant increases with loading were seen largely in the T2 of controls and less frequently in subjects with OA. In the medial posterior horn, T1ρ and T2 decreased with loading in OA but changed negligibly in controls; these significantly different loading responses between groups may indicate load transmission failure in OA menisci. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:249–261, 2016.